Réponses

Meilleure réponse !
  • carys
  • Modératrice confirmée
2013-03-11T20:52:03+01:00

G = 6²  - ( 4 - 2x ) + 1        

G = 6²  - ( 4 - 2*2 ) + 1    

G = 36 + 1

G = 37

 

H = y² - 3y + 7              

H = (-4)² - 3*(-4) + 7

H = 16 + 12 + 7

H = 35

 

voilà :)

2013-03-11T21:12:35+01:00

G = 6² -(4 -2x) +1                         pour x = 2

G = 6² - (4 -2X 2) +1

G = 36 - ( 4 -4) +1

G = 36 -0 +1

G = 37

 

H = y² -3y +7                              pour y = -4

H = -4² -3X -4 +7

H = 16 +12 +7

H = +35